Poverty alleviation programmes and ruralization of corruption in Nigeria: A case study of Community and Social Development Programme (CSDP) in Edo State - Ebonine, Victor Chukwugekwu; Kadiri, John Aigboje (Dynamics of Rural Society Journal, 2025)
Despite being endowed with an abundance of material and human resources, Nigeria still experiences growing poverty indexes and effects that include malnutrition, inflation, mortality rate, school dropouts, and lack of access to basic infrastructure. Past governments tried to address these challenges by introducing various forms of poverty alleviation programmes, particularly in rural areas. Yet, the programmes failed to achieve the expected outcomes with numerous factors adduced as reasons for their failures. Prominent among the reasons was the adoption of a top-down approach that prioritized corruption, elite primitive accumulation, and project abandonment, which culminated in the continuous impoverishment of the Nigerian people; hence, the adoption of a CSDP-driven bottom-up approach that prioritizes community participation. The objective of this study was to examine whether the widespread corruption that previously hindered the success of programs is still evident in this current program. The study deployed the elite theory to demonstrate elite sabotage of poverty alleviation initiatives in the Nigerian rural areas. The study employed an in-depth interview to gather responses from 109 participants knowledgeable about the various CSDPs located across the selected communities. The participants were selected using both simple random and snowball sampling techniques. The paper found that in the planning and implementation of CSDPs, two forms of corruption were manifest - power politics and fund mismanagement. These two forms of corruption were mutually exclusive and exposed the symbiotic relationship that existed between the state (elites) and the society in the politics of corruption in Nigeria. The study, therefore, recommends that the government encourage the participation of whistleblowers, civil society organizations, the media, the police, and the judiciary in anti-corruption efforts in rural areas of Edo State and, by extension, Nigeria.